Second-line chemotherapy rechallenge in lung cancer patients: a Moroccan real-world study - Tafenzi, Hassan Abdelilah; Choulli, Farah; Essadi, Ismail; Belbaraka, Rhizlane (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors are the go-to therapeutic option for relapsed non-small cell lung cancer (NSCLC) with unidentified oncogenic drivers when first-line platin doublet chemotherapy fails. Meanwhile, few options exist for the treatment of relapsed patients with small cell lung cancer (SCLC). Through the present study, we evaluate the efficacy and hematologic safety of rechallenging chemotherapy in the second line after the failure of platinum-based chemotherapy.MethodsIn this retrospective study, we selected patients admitted to a single institution. Adults aged > 18 years with a pathologically proven diagnosis of either NSCLC or SCLC, a PS of 2 or lower, and whose disease progressed during or after a platin-based doublet chemotherapy-containing line of treatment were eligible. The primary outcomes were second-progression-free survival (PFS) and overall survival (OS). Secondary endpoints included the proportion of patients with an overall response (complete or partial response), the disease control rate (DCR), and hematological safety.ResultsBetween January 2013 and December 2022, 155 patients were enrolled and treated in the second line with different available regimens of whom 145 had NSCLC and 10 had SCLC. As of December 31st, 2022, the median follow-up for the entire cohort was 4.6 [IQR: 2, 9.1] months. Overall, in the NSCLC patients, there was no statistical significance between the tested second-line regimens; the median PFS was 4.5 (95% CI: 3.6, 6.2) months (hazard ratio for progression: 1.1; 95% CI: 0.65, 1.86; p = 0.78), and the median OS was 10 (95% CI: 7.8, 16) months (hazard ratio for death: 1.49; 95% CI: 0.63, 3.54; p = 0.4). For the SCLC patients, we noticed the absence of statistical significance between treatment groups; the median PFS was 5.1 (95% CI: 1.9, Not Estimable [NE]) months (hazard ratio for progression: NE; p = 0.06), while statistical significance has been noticed between treatment groups in terms of proving OS; 5.1 (95% CI: 1.9, NE) months (hazard ratio for death: NE; p = 0.03). The overall response rate has not been reached (complete response = 0%; 2 patients have a partial response), and the disease control rate was 6.9% (n = 9) in the NSCLC population and 20% in the SCLC population. The most common grade 3–4 adverse hematological abnormalities were anemia (n = 30, 19.2%), neutropenia (n = 19, 12.3%), and thrombocytopenia (n = 14, 9.1%).ConclusionAt progression during or after first-line chemotherapy plus platinum, re-challenging single-agent chemotherapy in monotherapy or erlotinib did not offer modest activity in the Moroccan population.